Sprint running mechanics: A case study of a world-class athlete - Morin, J.-B.; Bourdin, M.; Edouard, P.; Peyrot, N.; Samozino, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
To date very few experimental data have been obtained directly on world-class sprinters. The recent validation of a sprint instrumented treadmill (Morin et al., 2010) allowed us to introduce the concept of effectiveness of force application throughout sprint acceleration and to show its relationship with 100-m performance in non-specialists (Morin et al., 2011). We tested here our recent hypothesis that the forward orientation of the resultant force onto the ground was better related to sprint performance than its magnitude, in a population including a sub-10 s individual. Methods The biomechanics and field 100-m performance of a world-class sprinter (WCS, 2011 best times of 9.92 s and 19.80 s on the 100-m and 200-m, respectively) were tested and compared to those of three national-level sprinters (NLS), and nine physical education students (PE). Subjects performed 6-s sprints on an instrumented treadmill during which horizontal, vertical and resultant ground reaction forces (GRF), and belt velocity were continuously recorded and used to compute linear force-velocity relationships. An index of the force orientation effectiveness (DRF) was also computed as the slope of the linear relationship between the decrease in the ratio of contact-averaged horizontal-to-resultant GRF and the increase in velocity (Morin et al. 2011). A 100-m field sprint was also performed with performances were recorded with a radar. Results WCS differed by more than 2 SD from the NLS and 2 to 4 SD from the PE for the slope of his force-velocity relationship (~25 % more oriented towards velocity muscular qualities), his ability to orient the resultant GRF forward during acceleration (~43 % better DRF) and his step frequency (~5 % higher, resulting only from a lower contact time). Contrastingly, he did not differ from NLS and some of the PE for the magnitude of resultant force produced. Discussion The main mechanical determinants characterizing this WCS were (i) a "velocity-oriented" force-velocity profile, likely explained by (ii) a higher ability to apply the resultant GRF vector with a forward orientation over the acceleration. Despite similar resultant force capabilities compared to NLS and PE, the WCS showed a better forward orientation of the resultant force onto the ground during acceleration, which confirmed our recent hypothesis that what matters to acceleration and sprint performance is more the orientation of the resultant force than its magnitude.